Institutional investor heterogeneity and analyst recommendation: Malaysian evidence - Ameen Qasem; Norhani Aripin; Wan Nordin Wan-Hussin; Shaker Dahan Al-Duais (Cogent Business & Management, 2021)
This study investigates the association between institutional investors' ownership and sell-side analysts' stock recommendations in the context of the heterogeneous nature of institutional investors. Based on a sample of 281 Malaysian public listed companies over the period 2008-2013 (732 company-year observations), we find a significant positive relationship between institutional ownership, in particular ownership held by privately managed institutional investors and sell-side analysts' stock recommendations, but no significant relationship between state owned institutional investors and sell-side analysts' stock recommendations. This suggests that the relationship between institutional investors and analysts' stock recommendations are different among different types of institutional investor. Our results are robust to tests for potential endogeneity between institutional ownership and analysts' stock recommendations.
Keywords: G20; G24; G30; G32; M41; 650; Institutional investors; sell-side analysts; stock recommendations; Malaysia